PELAKSANAAN TEKNIK PERMAINAN SCRABBLE DALAM PEMBELAJARAN VOCABULARY - Wildan Iskandar Lubis; Lollo Rosa Lubis; Rika Sri Erdila; Ulfa Hakiki; Lailatussiva Siregar (Institut Pendidikan Tapanuli Selatan, 2022)
The purpose of this community service activity is to assist students by applying scrabble games in learning in the community and to produce new English vocabulary for children in the community. This activity was carried out in one of the Wek IV neighborhoods on Jalan Sutan Hasanuddin. The target participants are community children. The method used is the theoretical and practical method of the game of scrabble. The results obtained through this training are innovative learning knowledge with scrabble games and children's ability to implement scrabble games to increase children's knowledge vocabulary to bind children's ability to pronounce words through scrabble games proves that the game can improve children's ability to pronounce words, numbers and linking words, as evidenced by the significant increase in vocabulary after community children used scrabble games in English learning or excellent vocabulary learning for four days of meetings.